2014
DOI: 10.1093/eurheartj/ehu046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of apixaban compared with warfarin according to age for stroke prevention in atrial fibrillation: observations from the ARISTOTLE trial

Abstract: AimsThe risk of stroke in patients with atrial fibrillation (AF) increases with age. In the ARISTOTLE trial, apixaban when compared with warfarin reduced the rate of stroke, death, and bleeding. We evaluated these outcomes in relation to patient age.Methods and resultsA total of 18 201 patients with AF and a raised risk of stroke were randomized to warfarin or apixaban 5 mg b.d. with dose reduction to 2.5 mg b.d. or placebo in 831 patients with ≥2 of the following criteria: age ≥80 years, body weight ≤60 kg, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
214
0
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(260 citation statements)
references
References 20 publications
17
214
0
29
Order By: Relevance
“…Of these patients, 790 were 75 years of age or older, the age group representing the majority of patients in the study reported here. In analyzing the ARISTOTLE subgroup of elderly patients within the slightly larger subgroup of patients receiving 2.5 mg PO bid, Halvorsen and others 8 found no difference in rates of stroke or systemic embolism and lower rates of major bleeding between patients receiving 2.5 mg PO bid and those receiving warfarin. However, because this age-based subgroup was quite small, it is difficult to be confident that the dosage of 2.5 mg PO bid would reduce the risk of stroke in patients who do not meet the specified criteria for this dosage.…”
Section: Discussionmentioning
confidence: 97%
“…Of these patients, 790 were 75 years of age or older, the age group representing the majority of patients in the study reported here. In analyzing the ARISTOTLE subgroup of elderly patients within the slightly larger subgroup of patients receiving 2.5 mg PO bid, Halvorsen and others 8 found no difference in rates of stroke or systemic embolism and lower rates of major bleeding between patients receiving 2.5 mg PO bid and those receiving warfarin. However, because this age-based subgroup was quite small, it is difficult to be confident that the dosage of 2.5 mg PO bid would reduce the risk of stroke in patients who do not meet the specified criteria for this dosage.…”
Section: Discussionmentioning
confidence: 97%
“…In Table 3 we report the main efficacy and safety end-points on older patients derived from age group subanalyses of the aforementioned phase III RCTs [74][75][76][77][78], discussed in more detail in the following sections.…”
Section: Evidence From Randomized Clinical Trialsmentioning
confidence: 99%
“…When efficacy and safety of AP were compared to warfarin according to age [76], although rates of stroke, all-cause death, and major bleeding were higher in the older age groups (p b 0.001 for all), AP was more efficacious than warfarin in preventing stroke and reducing mortality across all age groups, and was associated with less total and major bleedings, and less intracranial hemorrhages regardless of age (p for interaction 0.11 for all). Results were also consistent for the 13% of patients ≥ 80 years [76].…”
Section: Evidence From Randomized Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…U drugoj subanalizi pokazana je superiornost apiksabana u prevenciji moždanog udara i sistemskog tromboembolizma kod bolesnika sa različi-tim stepenom bubrežne insuficijencije, kao i sniženje . Dalje subanalize ARISTOTLE studije su pokazale da na efikasnost i bezbednost apiksabana ne utiče starost bolesnika (uključujuči pacijente starije od 80 godina) 37 , prisustvo koronane bolesti 38 , konkomitantna terapija aspirinom 39 , kvalitet regulacije INR-a 40 , klinički oblik AF (paroksizmalna, perzistentna ili permanentna AF) 41 ili prisustvo srča-ne insuficijencije (sa ili bez redukovane sistolne funkcije leve komore) 42 . Apiksaban se može smatrati efikasnom i bezbednom alternativom varfarinu za pripremu bolesnika za elektivnu DC kardioverziju AF 43 .…”
unclassified